(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Post-COVID-19 patients experience long-lasting systemic effects that impair bone healing. Age-related comorbidities such as cardiovascular, endocrine, and genitourinary diseases complicate the recovery process after bone fractures. This article provides scientific research information on age-related concomitant diseases and surgical treatment of delayed healing of fractures after COVID-19.